Comparison of Business Law in Developing and Developed Countries: A Case Study of Indonesia and Singapore - Siregar, Boni; Giawa, Fransisko; Ginting, Meilani Amanda br.; Situmorang, Olyhabana (Manunggal Halim Jaya, 2025)
This study aims to compare the characteristics of business law between countries, namely Indonesia and Singapore. Indonesia and Singapore have different legal systems; Indonesia uses civil law while Singapore uses common law, which affects regulations in business activities between the two countries. This study focuses on three main aspects: corporate regulation, intellectual property rights, and investor protection. This study found that Singapore is superior in terms of legal certainty and efficiency, while Indonesia still faces challenges in implementing regulations that often change. The results of this study are expected to provide further understanding of the implications of different legal systems and become input for policymakers in Indonesia in improving the investment climate.